MIXED GONADAL DYSGENESIS WITH ISODICENTRIC Y CHROMOSOMES: A CASE SERIES - Anand, L Alexis; Wong, Jeanne Sze Lyn; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Isodicentric Y chromosomes are formed by intrachromosomal recombination or fusion of sister chromatids following Y chromosome breakage. CASES Case 1 A four-month-old male with ambiguous genitalia had a stretched penile length (SPL) of 2.4 cm, glandular hypospadias, palpable right gonad and empty left scrotum. External genitalia score (EGS) was 7 and external masculinization score (EMS) was 6.5. Investigation showed normal 17-OHP [33.04 nmol/L, reference value (RV) 12-36], ACTH (2.1 pmol/L, RV 1.6-13.9) and s erum cortisol (239.15 nmol/L, RV 145-619); and elevated renin (>550 mU/L, RV 4-89). He was in mini-puberty at three months, with LH 1.7 mU/mL, FSH 5.4 mU/mL, testosterone 3.14 nmol/L and anti-Müllerian hormone (AMH) 350.3 pmol/L (RV 235.5-1125.9). Ultrasonography showed a right testis with empty left scrotal sac and no Müllerian structures. Karyotype revealed 73% (45,X) and 27% (46,X idicY) p11.2 with isodicentric chromosome Yq. Case 2 A four-month-old male presented with ambiguous genitalia, SPL 2.5 cm, perineal hypospadias, palpable right testis at the inguinal region, impalpable left testis, EGS 5.5 and EMS 5.5. Work-up showed normal 17-OHP (19.9 nmol/L) and serum cortisol (255 nmol/L); and elevated aldosterone (>3656 pmol/L) and renin (128.9 mU/L). Investigations post-delivery revealed mini-puberty with LH 6.59 IU/L, FSH 4.84 IU/L, testosterone 5.86 nmol/L and estradiol 43 pmol/L. AMH at 4 months was 435.8 pmol/L. Abdominal ultrasonography showed embedded penis with bilateral inguinal testes and no Müllerian structures. FISH with SRY gene probe revealed the first cell line (74.5%) of isodicentric chromosome Y and the second cell line (25.5%) of 45,X. Conclusion Patients with isodicentric Y chromosomes have various presentations necessitating follow-up to monitor growth, puberty, fertility, gonadal dysgenesis and short stature.